PTH-064 Closing The Audit Loop Without Solving the Problem: Inappropriate Faecal Calprotectin Requests Continue Despite Agreed Guidelines. (17th August 2016) - Parr, H; Rampton, D; Macdonald, D; Scott, C
Abstract : Introduction: As a non-invasive marker of intestinal inflammation, faecal calprotectin (FCP) is widely used to minimise colonoscopy requests in patients presenting with diarrhoea and to monitor patients with established inflammatory bowel disease (IBD). We performed two successive audits of how well gastroenterologists in a specialist IBD unit adhere to defined agreed guidelines about the indications for FCP. Methods: In mid 2014, we devised and circulated 3 criteria for requesting FCP. In early 2015, we audited the adherence of 45 successive requests for FCP to these criteria. On the basis of the results (below), we revised and recirculated the guidelines in early 2015, including 2 further criteria. In late 2015, we completed the audit loop by reviewing 80 recent FCP requests. Results: The table shows the numbers of appropriately requested FCPs, as a percentage of all requests for each indication. The guidelines in italics are those added following the initial audit. There was a slight improvement in quality of requests for FCP between the first and the second audit. The most frequent and serious issue in FCP ordering was the requesting of colonoscopy simultaneously (15/80 in 2015) and/or ignoring of recent colonoscopy results (5/80 in 2015). There were no abnormal colonoscopies reported when FCP was normal. Consultants, SpRs and IBD nurses were equally prone to making inappropriate FCP requests. Conclusion: Despite being issued with guidelines agreed and revised as a result of an initial audit, specialist clinicians continue to request FCP inappropriately. This results in avoidable colonoscopy and consequent unnecessary unpleasantness for patients and expense for health-care providers. Guidelines about when to request FCP need more effective dissemination and requests for colonoscopy should be vetted more stringently. Disclosure of Interest: None Declared